Subscapularis tendinopathy is highly prevalent in elite swimmer's shoulders: an MRI study - Holt, K.; Delbridge, A.; Josey, L.; Dhupelia, S.; Livingston, G. C.; Waddington, G.; Boettcher, C. (Journal of Science and Medicine in Sport, 2022)
Objectives: The aim of this study is to determine the prevalence of abnormal anatomical change present on MRI in elite swimmers' shoulders compared to age-matched controls. Design: Descriptive epidemiological study. Methods: Sixty (aged 16-36years) elite Australian swimmers and 22 healthy active, age and gender matched controls (aged 16-34years). All participants completed a demographic, and training load and shoulder pain questionnaire and underwent shoulder MRI. Tests for differences in the population proportion was used for comparison between swimmers dominant and non-dominant shoulders and those of the controls. Results: Subscapularis and supraspinatus tendinopathy was the most common tendon abnormality identified in swimming participants, being reported in at least one shoulder in 48/60 (73%) and 46/60 (70%) swimmers, respectively. There was no significant difference between dominant and non-dominant shoulders for either tendinopathy, however, grade 3 tendinopathy was significantly more prevalent in subscapularis than in supraspinatus (P<0.01). Compared with controls, significantly more abnormalities were reported in swimmers' shoulders in both subscapularis and supraspinatus tendons along with the labrum and acromioclavicular joint. Pathology was not a predictor of current pain. Conclusions: This data confirms that tendon abnormality is the most common finding in elite swimmers' shoulders. Furthermore, that subscapularis tendinopathy is not only as common as supraspinatus but has a greater prevalence of grade 3 tendinopathy. With significant varied abnormalities including tendinopathy being so common in both symptomatic and asymptomatic shoulders of swimming athletes', clinicians should consider imaging findings alongside patient history, symptom presentation and clinical examination in determining their relevance in the presenting condition.